2020
DOI: 10.1093/icvts/ivaa077
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic aortic computed tomography angiography in swine: establishment of a baseline for endovascular evaluation of the ascending aorta

Abstract: OBJECTIVES Our goal was to establish a baseline of computed tomography (CT) angiographic data for the porcine ascending thoracic aorta for endovascular evaluation of animal experiments and device development. METHODS Thoracic aortic CT angiography was conducted on 49 pigs with an average body weight of 60–65 kg. The CT angiographic scans were done on an imaging reconstruction workstation to obtain the specific aortic geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Such an analysis can have indeed implications in the field of 3R (replacement, reduction, refinement) 42 using this in silico analysis as surrogate the porcine model used for pre-clinical tests of TEVAR endograft. 43 At the same time, the present study provides further insights on the TEVAR biomechanics. The developed experimental framework allows to measure the PWV and the corresponding results highlight that the presence of the stent-graft induces an increase of PWV underlining the stiffening of the aortic structure.…”
Section: Discussionmentioning
confidence: 59%
“…Secondly, at the best our knowledge, the present study is the first one that addresses the FEA analysis of endograft deployment in a porcine aorta. Such an analysis can have indeed implications in the field of 3R (replacement, reduction, refinement) 42 using this in silico analysis as surrogate the porcine model used for pre‐clinical tests of TEVAR endograft 43 . At the same time, the present study provides further insights on the TEVAR biomechanics.…”
Section: Discussionmentioning
confidence: 73%
“…For plastic viscosity, when the pumping agent content exceeds 2%, the decrease begins to slow down obviously. Tao et al [6], aiming at the problems of poor rheological stability, delamination in slurry and pipe blockage caused by coarse aggregate settlement in longdistance filling slurry of pumped large double line in coal mine filling mining, measured the fluidity value and fluidity loss with time of four groups of filling slurry by using the fluidity loss experiment method. On the basis of diffusion theory, Li [7] deduced the vertical distribution formula of coarse aggregate filling slurry concentration, considering the factors of solid particle size, particle shape and density, slurry density, and yield stress.…”
Section: Introductionmentioning
confidence: 99%